Preliminary evaluation of microbiological quality in fried rice sold in Kuantan city, Malaysia - Abu Bakar, Ibrahim; Abdul Rafa, Ainin Azwani; Abdullah Sani, Norrakiah; Jaswir, Irwandi; Saeed Mirghaini, Mohamed Elwathig (2013)
Food contamination is a crucial health problem as it could result in food-borne illness. This research aimed to evaluate the microbiological quality in ready-to-eat fried rice dish sold at different type of food premises in Kuantan city, Pahang. Colony forming unit (cfu) in Aerobic colony count, Staphylococcus aureus, and Bacillus cereus were utilized as bacteriological contamination indicators. About 52 samples were collected stratified randomly from four types of food premises (restaurant, cafeteria, stall and night market) where about 13 samples were collected from each type of food premises respectively. The microbiological quality of the fried rice was compared to the local microbiological guidelines for ready-to-eat foods formulated by Ministry of Health Malaysia and other international guidelines. The counts for aerobic colony count were in the range 10-5 to 10-6 CFU/g. Meanwhile S.aureus was in the range 10-4 to 10-5 CFU/g and B.cereus 10-5 to 10-7 CFU/g and all the counts were exceed the proposed guidelines.